Measurement of Bioaccumulation of Some Heavy Elements in Sinanodonta woodiana and Corbicula fluminea In Al-Gharaf River,Thi-Qar Governorate, Iraq - Mashjel, Zainab H; Al-Taher, Qasim M (Technium BioChemMed, 2025)
The current study was conducted in the period October 2023 to September 2024, the study aimed to measure the concentrations of some heavy metals in water and sediments and their bioaccumulation in the soft tissues of two species of molluscs Corbicula fluminea and Sinanodonta woodiana Water samples, sediments and molluscs were collected from four stations on the Gharraf River in southern Iraq and the order of the elements in the water was Pb>Zn>Ni>Cu>Cd>Cr>As and in the sediments Ni>Zn> Cu> Pb >Cr >Cd >As and in C.fluminea was Zn>Ni>Pb>Cu>Cr>Cd>As and in S.woodiana was Ni>Zn>Pb>Cu>Cr>Cd>As The highest concentrations of elements were recorded in the third and fourth stations and the concentrations were in the first and second stations The results showed seasonal variation in the concentrations of elements in the water, sediments and soft tissues of molluscs in the Gharraf River, which indicates high rates of pollution in its water.